PEMBANDINGAN KEKUATAN TARIK TULANGAN DENGAN MENGGUNAKAN ALAT BRINEL DAN MENGGUNAKAN UTM (UNIVERSAL TEST MACHINE) - Fiki Priansyah; Indra Bachtiar; Rinawati Rinawati (Politeknik Negeri Jakarta, 2012)
Brinnel portable equipment is the most practical tool used in the field to determine the tensile strength of reinforcement. Basically brinnel validity of the tool is still very doubtful, as well as tools that existed at the Laboratory brinnel State Polytechnic of Jakarta. Based on these problems, research needs to determine the validity of the tool. The research was conducted by comparing the tensile strength test results between testing with tools brinnel and with UTM (Universal Test Machine). This test uses a test specimen plain rebars of 8 mm and 10 mm and 10 mm threaded bars, 13 mm and 16 mm. The length of the test object for testing using the UTM is 300 mm while for testing using a tool which is 700 mm brinel. From the test results comparing the data obtained between the tensile strength testing using the UTM and testing using tools brinnel. From testing the difference of tensile strength test results are quite significant. Testing with tools brinnel have lower results than testing with UTM with a difference of about 30%. Keywords: tensile strength, brinnel tools, Universal Test Machine